PERBEDAAN PERILAKU (PENGETAHUAN, SIKAP DAN PRAKTIK) SISWA YANG MEMPEROLEH DAN BELUM MEMPEROLEH PENDIDIKAN KESEHATAN REPRODUKSI TAHUN 2017 - Rifha Asti Hardinawanti; Sri Achadi Nugraheni; Atik Mawarni; Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2018)
According to PKBI, who had premarital sexual intercourse reached 98 (26%), prenuptial marriage reached 85 (21%), and in the year 2011 who had premarital sexual intercourse reached 193 (20%), prenuptial pregnancy reached 79 (9%), 52 % of teenagers who had premarital sexual intercourse ranged in age from 15-19 years. One of the causes of the emergence of various problems of adolescent reproductive health is due to the students knowledge about reproductive health is still low. The aim of this study was to analyze differences in behavior (knowledge, attitudes and practices) of students who obtained and have not received reproductive health education. Type of research explanatory research with cross sectional study design. The population in this study was 469 students with simple random sampling technique and got 77 samples for each school. The results showed the percentage of students with less knowledge that is 6.5% (not getting education) 2.6% (got education). Percentage of students with attitude less 55,8% (not getting education) 40,3% (got education).Percentage of students with less practice 48.1% (not getting education) 36.4% (got education).Data analysis using Mann-Whitney test to see the difference of knowledge, attitude, and practice of reproductive health of students. The result of the statistical test shows that there are differences of knowledge in schools that have not received reproductive health education (p-value = 0.001), there are different attitudes in schools that have not received reproductive health education (p-value = 0.001) practices in schools receiving and not receiving reproductive health education (p-value = 0.024). this research suggested that there should be improvement of material on reproduction health for every high school (SMA).